2017
DOI: 10.3390/f8030088
|View full text |Cite
|
Sign up to set email alerts
|

Salvage-Logging after Windstorm Leads to Structural and Functional Homogenization of Understory Layer and Delayed Spruce Tree Recovery in Tatra Mts., Slovakia

Abstract: Stand-replacing disturbance and post-disturbance salvage-logging influence forest succession in different ways; however, limited knowledge regarding how salvage-logging affects vegetation patterns compared to natural development of forest ecosystems is still lacking. In this study, we described the diversity pattern of understory vegetation and tree regeneration in mountain spruce forest of Tatra Mountains, northern Slovakia, where a high severity windstorm affecting over 10,000 ha occurred in 2004. The area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Changes in EIVs after the cutting treatments were most significant for light; plot-level EIV-L increased in both the 50% and 100% cutting. This is because of the increased richness and cover of early successional light-demanding species in management-created canopy gaps, a general pattern occurring in post-management conditions [68]. Mean EIV-F significantly decreased in canopy gaps (Figure 5d), indicating that some plant species that were more adapted to drier soil conditions colonized the gaps.…”
Section: Ecological and Trait-based Perspectivementioning
confidence: 94%
“…Changes in EIVs after the cutting treatments were most significant for light; plot-level EIV-L increased in both the 50% and 100% cutting. This is because of the increased richness and cover of early successional light-demanding species in management-created canopy gaps, a general pattern occurring in post-management conditions [68]. Mean EIV-F significantly decreased in canopy gaps (Figure 5d), indicating that some plant species that were more adapted to drier soil conditions colonized the gaps.…”
Section: Ecological and Trait-based Perspectivementioning
confidence: 94%
“…Salvage logging certainly favored also high abundance of grasses. Several studies identified higher species richness and cover of graminoids at salvage-logged compared to non-intervention sites which likely triggered also different successional trajectories of post-disturbance herb layer vegetation [11,51,52]. Decline of grasses identified in our study possibly induces a compositional convergence of salvage-logged and non-intervention sites, however, our study did not examine successional processes following different management approaches, thus further research is needed to verify this assumption.…”
Section: Status and Temporal Changes In Post-disturbance Vegetationmentioning
confidence: 62%
“…However, the period of four years our study is based on is likely too short to observe any significant changes. Perhaps, this might be related to lower levels of spatial heterogeneity [52] and also faster homogenization of young forest structure [53] at salvage-logged sites as this type of post-disturbance management was applied at our transects. Salvage logging certainly favored also high abundance of grasses.…”
Section: Status and Temporal Changes In Post-disturbance Vegetationmentioning
confidence: 99%
“…At the initial stage of an outbreak, sanitary management may prove effective. When a bark beetle outbreak reach an epidemic stage, the rate of sanitary cutting in the buffer zone may lead to large areas that have clear cuts and changed paths for forest succession in the buffer zone (Michalová et al 2017). In this case, decisionmaking bodies face a tough decision: either they should continue to use sanitary management in the buffer zone or they should look for other solutions, such as changes in the zonation of a protected area.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of bark beetle epidemics in the core zone of a national park, these buffer zones can act as a bulwark against the spread of bark beetle infestations into managed forests. However, removal of wind-thrown trees can alter successional pathways compared to no-intervention areas (Michalová et al 2017;Thorn et al 2017); there is pressure from forest owners outside the park to stop or slow the spread of bark beetle outbreak leading to bark beetle suppression in the buffer zone. The highest intensity of sanitary management will usually focus on this area.…”
Section: Introductionmentioning
confidence: 99%